On the prediction of the yield stress of unimodal and multimodal γ′ Nickel-base superalloys. (1st October 2015) - Galindo-Nava, E.I.; Connor, L.D.; Rae, C.M.F.
Graphical abstract: Abstract: A new model for the yield stress in superalloys accounting for unimodal and multimodal γ ′ size distributions is presented. A critique of the classic models on γ ′ shearing is presented and important features not previously considered are incorporated in our model. This is extended to account for multimodal particle size distribution effects by weighting the individual particle contribution to the total strength. This analysis is focused on powder metallurgy alloys. The yield stress and particle strengthening are predicted for eight superalloys containing wide variations in initial microstructure, composition and at temperatures up to 700 °C. We demonstrate through a theoretical approach that the strength of alloys with multimodal γ ′ is lower than those with unimodal γ ′ radius in the vicinity of 10–30 nm. For the first time, a parameter-free physics-based model is able to predict the yield stress in superalloys with complex microstructures, including unimodal and multimodal γ ′ size. This has been possible by removing limitations inherent to the classical models. Such approach also enables critical evaluation of the relevant factors contributing to the yield strength of polycrystalline superalloys.